Random auxetics from buckling fibre networks - S. Domaschke (Nature Portfolio, 2019)
Auxetic materials have usually been developed with periodically arrange structures. Here, the authors electrospin fibre networks, and show both theoretically and experimentally that these random structures have pronounced auxetic behaviour with negative out-of-plane Poisson’s ratio of large magnitude.